Sosialisasi Penerapan Media Interaktif Untuk Klasifikasi Puisi Indonesia Berdasarkan Gaya Bahasa - Atika Sadariah; Melati Rahma Suri; Indah Cahyani (Sevaka : Hasil Kegiatan Layanan Masyarakat, 2023)
The application of interactive media in classifying Indonesian poetry based on stylistic devices aims to enhance students' understanding in identifying and analyzing the stylistic elements used in poetry. Stylistic devices such as metaphors, personification, hyperbole, and similes play a significant role in enriching the meaning of poetry and deepening the reader’s interpretation. The use of interactive media offers a more dynamic and effective approach compared to traditional methods. Through digital platforms and interactive learning applications, students can become more engaged in an active and enjoyable learning process, making it easier for them to recognize and comprehend various stylistic devices in poetry. This media also supports diverse learning styles, such as visual, auditory, and kinesthetic, enabling students to learn according to their preferences. This study aims to explore the effectiveness of interactive media in teaching the classification of stylistic devices in poetry and how it can enrich the learning experience while improving students' analytical skills in literary works. It is hoped that the application of interactive media can create a more engaging learning environment, boost students' motivation, and deepen their understanding of Indonesian poetry.